A high‐throughput shotgun mutagenesis approach to mapping B‐cell antibody epitopes. Issue 1 (September 2014) - Davidson, Edgar; Doranz, Benjamin J.
Summary Characterizing the binding sites of monoclonal antibodies (mAbs) on protein targets, their 'epitopes', can aid in the discovery and development of new therapeutics, diagnostics and vaccines. However, the speed of epitope mapping techniques has not kept pace with the increasingly large numbers of mAbs being isolated. Obtaining detailed epitope maps for functionally relevant antibodies can be challenging, particularly for conformational epitopes on structurally complex proteins. To enable rapid epitope mapping, we developed a high‐throughput strategy, shotgun mutagenesis, that enables the identification of both linear and conformational epitopes in a fraction of the time required by conventional approaches. Shotgun mutagenesis epitope mapping is based on large‐scale mutagenesis and rapid cellular testing of natively folded proteins. Hundreds of mutant plasmids are individually cloned, arrayed in 384‐well microplates, expressed within human cells, and tested for mAb reactivity. Residues are identified as a component of a mAb epitope if their mutation (e.g. to alanine) does not support candidate mAb binding but does support that of other conformational mAbs or allows full protein function. Shotgun mutagenesis is particularly suited for studying structurally complex proteins because targets are expressed in their native form directly within human cells. Shotgun mutagenesis has been used to delineate hundreds of epitopes on a variety of proteins, including G protein‐coupled receptor and viral envelope proteins. The epitopes mapped on dengue virus prM/E represent one of the largest collections of epitope information for any viral protein, and results are being used to design better vaccines and drugs.